2019
DOI: 10.1029/2019jc015305
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Small Phytoplankton Contribution to the Total Primary Production in the Amundsen Sea, Antarctica

Abstract: The importance of small phytoplankton in warming and stratified water conditions has been emphasized, but little information on the small phytoplankton contribution is currently available in the Southern Ocean. In this study, we analyzed temporal variations in the carbon uptake rates of large and small phytoplankton and the small phytoplankton contributions to the total primary production. The data were collected in the Amundsen Sea polynya region using three different field observations (early January, Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 84 publications
(184 reference statements)
2
19
1
Order By: Relevance
“…(2013) and Lim et al. (2019) observed lower specific carbon uptake rates (h −1 ) for small phytoplankton than for large phytoplankton in the Arctic and Antarctic Oceans. In fact, Jang et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(2013) and Lim et al. (2019) observed lower specific carbon uptake rates (h −1 ) for small phytoplankton than for large phytoplankton in the Arctic and Antarctic Oceans. In fact, Jang et al.…”
Section: Discussionmentioning
confidence: 92%
“…Low primary production rates are often observed under the picoplankton-dominant community structure in various oceans. Lee et al (2013) and Lim et al (2019) observed lower specific carbon uptake rates (h −1 ) for small phytoplankton than for large phytoplankton in the Arctic and Antarctic Oceans. In fact, Jang et al (2018) found that the relatively higher contributions of small phytoplankton to total primary production resulted in lower total primary production rates in the Yellow Sea.…”
Section: Table 2 the Comparison Of Total Chl A Biomass And The Contrimentioning
confidence: 91%
“…Observational and model studies on the impact of increasing small phytoplankton uptake suggest that primary productivity will decrease if small phytoplankton becomes the predominant species [24,[53][54][55][56]. Since our study did not include species identification and abundance, the discussion on species diversity is limited in this regard.…”
Section: Impact Of Small Phytoplankton On the Total Din Assimilation Ratesmentioning
confidence: 96%
“…This could be caused by the different primary productivities between pico-and large-sized (>2 µm) phytoplankton [22]. Generally, pico-sized phytoplankton have a lower primary productivity than large phytoplankton [14,22,70]. Therefore, the total primary production can be decreased by increasing contribution of pico-sized phytoplankton, with their lower productivity traits.…”
Section: Comparisons Of Primary Production Between This and Previous Studiesmentioning
confidence: 99%